Reward in Education from the Perspective of the Qur'an - Hirayu, Heru; Qadri, Ikhwanul; Ernita, Novi; Yulita, Desma; Hidayatullah, M.; Syafruddin, Syafruddin; Dona, Dori Rahma; Wesyunita, Wesyunita; Tussakdiah, Halimah; Gusnita, Sri (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
This paper presents the pros and cons among scholars regarding punishment as a method in education. The group in favor of using rewards argues that completely eliminating rewards can lead to positive outcomes. Among these, children may develop a sense of respect for parents and teachers, show more attention to the lessons taught, and become more concerned about values, norms, and applicable laws. The Qur'an contains many references to rewards. However, parents and teachers' understanding of rewards is often limited to punishment, with physical punishment being the primary choice. At times, the rewards given do not align with the guidance found in the Qur'an. This study uses library research with a maudhu'i (thematic) method. The analysis was conducted with the help of tafsir texts and educational books, and a conclusion was drawn. This research reveals that according to the indications of the Qur'an, a reward is a compensation or reward deliberately and consciously given by the educator to the student, which leads to awareness. The types of rewards that can be applied based on Qur'anic verses include non-physical punishment, as mentioned in Q.S. an-Nisa' verse 34, material punishment in Q.S. al-Maidah verse 89, and physical punishment in Q.S. al-Baqarah verses 178-179.